Analisis Perilaku Moral Hazard dan Adverse Selection pada Agency Problem di Pembiayaan Musyarakah PT. Bank Sumut KCPSY Binjai - Abdillah, Prayugo Ali; Imsar; Jannah, Nurul (Ikatan Da'i Indonesia, 2024)
This study aims to determine the form of behavior and how to handle agency problems caused by moral hazard behavior and adverse selection in musyarakah financing at PT. Bank Sumut KCPSY Binjai. The agency problem is the agency problem in the musyarakah product scheme. This type of research is field research with qualitative methods. Sources of data in this study include two categories, namely primary data and secondary data. The subjects in this study were employees of PT. Bank Sumut KCPSY Binjai in the management section that is competent in the field of musyarakah financing. The research results show that the form of moral hazard and adverse selection behavior at PT. Bank Sumut KCPSY Binjai namely the difficulty of banks assessing the true character of customers, errors in analysis, ethical deviations and lack of supervision (monitoring) carried out by banks. PT. Bank Sumut KCPSY Binjai Office made various efforts from screening, verification to monitoring. Furthermore, if the problem of moral hazard and adverse selection has occurred, the bank will handle it in two ways, namely saving financing in the form of first rescheduling, reconditioning, restructuring and solving problem financing by means of billing. lawsuits, execution of mortgage auctions, and WO